Compensatory growth in an aquatic plant mediates exploitative competition between seasonally tied herbivores - B Hidding; B Nolet; T de Boer; P de Vries; Marcel Klaassen (2009)
The degree to which vertebrate herbivores exploitatively compete for the same food plant may depend on the level of compensatory plant growth. Such compensation is higher when there is reduced density-dependent competition in plants after herbivore damage. Whether there is relief from competition may largely be determined by the life-history stage of plants under herbivory. Such stage-specific compensation may apply to seasonal herbivory on the clonal aquatic plant sago pondweed ( Potamogeton pectinatus L. ). It winters in sediments of shallow lakes as tubers that are foraged upon by Bewick's Swans ( Cygnus columbianus bewickii Yarrell ), whereas aboveground biomass in summer is mostly consumed by ducks, coots, and Mute Swans. Here, tuber predation may be compensated due to diminished negative density dependence in the next growth season. However, we expected lower compensation to summer herbivory by waterfowl and fish as density of aboveground biomass in summer is closely related to photosynthetic carbon fixation. In a factorial exclosure study we simultaneously investigated (1) the effect of summer herbivory on aboveground biomass and autumn tuber biomass and (2) the effect of tuber predation in autumn on aboveground biomass and tuber biomass a year later. Summer herbivory strongly influenced belowground tuber biomass in autumn, limiting food availability to Bewick's Swans. In contrast, tuber predation in autumn by Bewick's Swans had a limited and variable effect on P. pectinatus biomass in the following growth season. Whereas relief from negative density dependence largely eliminates effects of belowground herbivory by swans, aboveground herbivory in summer limits both above- and belowground plant biomass. Hence, there was an asymmetry in exploitative competition, with herbivores in summer reducing food availability for belowground herbivores in autumn, but not the other way around.